1997
DOI: 10.1074/jbc.272.26.16445
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase-dependent Activation of Protein Kinase C-ζ in Bacterial Lipopolysaccharide-treated Human Monocytes

Abstract: The isoform identity of activated protein kinase C (PKC) and its regulation were investigated in bacterial lipopolysaccharide (LPS)-treated human monocytes. Resolution of detergent-soluble lysates prepared from LPS-treated, peripheral blood monocytes using Mono Q anion-exchange chromatography revealed two principal peaks of myelin basic protein kinase activity. Immunoblotting and immunoprecipitation with isoform-specific anti-PKC antibodies showed that the major and latest eluting peak is accounted for by PKC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 34 publications
8
82
1
Order By: Relevance
“…Sajan et al (40) have linked PDK-1 and PKC to ERK activation by LPS in rat adipocytes. In a model closer to ours, Herrara-Velit et al (41) have shown that in LPS-treated monocytes, PKC activation is PDK-1 dependent. PKC activation requires autophosphorylation, phosphorylation of Thr 402 in the activation loop (probably by PDK-1), removal of the pseudosubstrate from the catalytic domain, and subcellular localization near a substrate (42).…”
Section: Discussionmentioning
confidence: 99%
“…Sajan et al (40) have linked PDK-1 and PKC to ERK activation by LPS in rat adipocytes. In a model closer to ours, Herrara-Velit et al (41) have shown that in LPS-treated monocytes, PKC activation is PDK-1 dependent. PKC activation requires autophosphorylation, phosphorylation of Thr 402 in the activation loop (probably by PDK-1), removal of the pseudosubstrate from the catalytic domain, and subcellular localization near a substrate (42).…”
Section: Discussionmentioning
confidence: 99%
“…PKC can be activated in vitro by phosphatidylinositol-3,4,5-triphosphat (42,56), phosphatidic acid (57), ceramide, and arachidonic acid (58,59), and/or by direct interaction with binding proteins (60). To activate PKC , phosphorylation of the activation loop consensus threonine residue Thr 410 by PI3K-induced phosphoinositide-dependent kinase 1 is substantial (41).…”
Section: Discussionmentioning
confidence: 99%
“…When the effects of PI3Ј-kinase inhibitors were studied, cells were incubated with 100 M LY294002, 100 nM wortmannin, or 40 M pseudoZ for 30 min before the addition of C a 2ϩ . PKC and / activities were measured by using minor modifications of previously published methods (Gomez et al, 1997;Herrera-Velit et al, 1997). After treatment, cells were washed in PBS and lysed for 1 hr at 4°C in 150 l of lysis buffer (1% Triton X-100, 20 mM Tris, pH 7.4, 150 mM NaC l, 1 mM EDTA, 2 mM EGTA, 1 mM Na-vanadate, 100 nM okadaic acid, 100 g /ml aprotinin, 100 g /ml leupeptin, 0.5 mM phenylmethanesulfonyl fluoride, 12.5 g /ml pepstatin, and 1 mM benzamide).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated that both nPKCs and aPKCs are activated by products of PI3Ј-kinase Toker et al, 1994;Derman et al, 1997;Herrera-Velit et al, 1997;Standaert et al, 1997;Chou et al, 1998). It is thus possible that PI3Ј-kinase is responsible for activating the pseudoZ-sensitive isoform of PKC (such as PKC ) after stimulation of the CaR.…”
Section: Pi3 -Kinase Participates In Signal Transduction From the Carmentioning
confidence: 99%